WORD FORMATION ANALYSIS FOUND IN ENGLISH SLANGS USED BY CARDI B ON INSTAGRAM - Sesil (English Literature Study Program of Universitas Kebangsaan Republik Indonesia, 2025)
This study aims to investigate the word formation processes found in English slang used in the Instagram captions posted by Cardi B. A qualitative descriptive method was employed to explore the linguistic features of slang expressions in Cardi B’s captions. The analysis is grounded in Yule’s theory of word formation processes. Data were collected using documentation techniques, involving close observation and careful transcription of textscontaining slang elements. The slang words identified were then classified according to theirword formation types and analyzed based on the relevant theoretical framework. The findings reveal that eight out of ten types of word formation processes proposed by Yule are present inCardi B’s Instagram captions. These include: (1) Clipping, (2) Derivation, (3) Coinage, (4)Blending, (5) Acronym, (6) Conversion, (7) Compounding, and (8) Borrowing. The most frequently occurring type was clipping, which appeared in 26 instances (52%). This suggeststhat Cardi B tends to favor concise word forms to create a casual, rapid, and easily understoodlinguistic style. Such a tendency reflects the informal nature of urban language, typical of socialmedia discourse and popular culture.